2019
DOI: 10.4038/sljch.v48i3.8754
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of junk food consumption, overweight/obesity and self-rated health and fitness in high school adolescent girls: a cross sectional study in a deprived area of Qom

Abstract: Background: Junk food intake is associated with high salt and high caloric intake and is one of the causes of overweight/obesity. Objectives: To assess the prevalence of junk food consumption in snack times and its association with obesity and overweight in high school girl students in a deprived area of Qom. Method: A cross-sectional study was done in 638 high school girls who were selected using the multistage random sampling method. Overweight/obesity was measured using body mass index (BMI) and a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
2
14
0
2
Order By: Relevance
“…Obesity/overweight was found to be positively linked to the frequency with which students consume fast food two or more times per week (AI-Otaibi & Basuny, 2015). Mohammadbeigi, et al (2019) found junk food consumption is linked to high salt and calorie intake and is one of the leading causes of overweight and obesity. This study found there was no significant association between gender and overweight/obesity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Obesity/overweight was found to be positively linked to the frequency with which students consume fast food two or more times per week (AI-Otaibi & Basuny, 2015). Mohammadbeigi, et al (2019) found junk food consumption is linked to high salt and calorie intake and is one of the leading causes of overweight and obesity. This study found there was no significant association between gender and overweight/obesity.…”
Section: Resultsmentioning
confidence: 99%
“…12% were overweight male students. The study done by Mohammadbeigi et al (2019) was based on high school adolescent girls and the result was there is no association between BMI & junk food consumption. Al-Otaibi and Basuny (2015) found that overweight/obesity is associated with fast food consumption of university female students.…”
Section: Gender and Overweightmentioning
confidence: 99%
See 3 more Smart Citations